Pemetaan Dan Pengukuran Pemanfaatan TIK Menggunakan Metode Echosystem (Studi Kasus STT-Payakumbuh) - Noviardi Noviardi; Dilson Dilson; Ranti Irsa (Elkawnie, 2016)
The rapid growth of ICT (Information and CommunicationTechnology), which changed the whole aspect of human life, such as the way people think, behave, communicate, work and support themselves. This change had a positive impact on the improvement of the efficiency of information and communication needs. So that the use of IT in all areas of life provides a significant advantage. Utilization of Information and Communication Technology (ICT) in the institution of Higher Education requires planning and management are mature, both in infrastructure, human resources and in terms of users, so that the use of ICT / ICT not only to improve the effectiveness, efficiency and productivity, but also can improve competitiveness (competitive adventages) in the era of globalization ini.Metode used in this study is a Echosystem consisting of three (3) stages of development that the ICT development by UNSECO, iT development, and the development model Zen Framework Smart Campus (TeSCA). It is hoped this method can be a strategic step in the utilization of and basis for the advancement of the ICT development of STT-Payakumbuh campus in the future